The Influence of Combined Turbulators on the Hydraulic-Thermal Performance and Exergy Efficiency of MWCNT-Cu/Water Nanofluid in a Parabolic Solar Collector: A Numerical Approach - Khetib, Yacine; Melaibari, Ammar; Alsulami, Radi (Frontiers in Energy Research, 2021)
The present research benefits from the finite volume method in investigating the influence of combined turbulators on the thermal and hydraulic exergy of a parabolic solar collector with two-phase hybrid MWCNT-Cu/water nanofluid. All parabolic geometries are produced using DesignModeler software. Furthermore, FLUENT software, equipped with a SIMPLER algorithm, is applied for analyzing the performance of thermal and hydraulic, and exergy efficiency. The Eulerian–Eulerian multiphase model and k-ε were opted for simulating the two-phase hybrid MWCNT-Cu/water nanofluid and turbulence model in the collector. The research was analyzed in torsion ratios from 1 to 4, Re numbers from 6,000 to 18,000 (turbulent flow), and the nanofluid volume fraction of 3%. The numerical outcomes confirm that the heat transfer and lowest pressure drop are relevant to the Re number of 18,000, nanofluid volume fraction of 3%, and torsion ratio of 4. Furthermore, in all torsion ratios, rising Re numbers and volume fraction lead to more exergy efficiency. The maximum value of 26.32% in the exergy efficiency was obtained at a volume fraction of 3% and a torsion ratio of 3, as the Re number goes from 60,000 to 18,000.